Self-assembling, pH-responsive nanoflowers for inhibiting PAD4 and neutrophil extracellular trap formation and improving the tumor immune microenvironment - Di Zhu; Yu Lu; Lin Gui; Wenjing Wang; Xi Hu; Su Chen; Yanming Wang; Yuji Wang (Elsevier, 2022)
Self-assembling carrier-free nanodrugs are attractive agents because they accumulate at tumor by an enhanced permeability and retention (EPR) effect without introduction of inactive substances, and some nanodrugs can alter the immune environment. We synthesized a peptidyl arginine deiminase 4 (PAD4) molecular inhibitor, ZD-E-1M. It could self-assembled into nanodrug ZD-E-1. Using confocal laser scanning microscopy, we observed its cellular colocalization, PAD4 activity and neutrophil extracellular traps (NETs) formation. The populations of immune cells and expression of immune-related proteins were determined by single-cell mass cytometry. ZD-E-1 formed nanoflowers in an acidic environment, whereas it formed nanospheres at pH 7.4. Accumulation of ZD-E-1 at tumor was pH-responsive because of its pH-dependent differences in the size and shape. It could enter the nucleus and bind to PAD4 to prolong the intracellular retention time. In mice, ZD-E-1 inhibited tumor growth and metastasis by inhibiting PAD4 activity and NETs formation. Besides, ZD-E-1 could regulate the ratio of immune cells in LLC tumor-bearing mice. Immunosuppressive proteins like LAG3 were suppressed, while IFN-γ and TNF-α as stimulators of tumor immune response were upregulated. Overall, ZD-E-1 is a self-assembling carrier-free nanodrug that responds to pH, inhibits PAD4 activity, blocks neutrophil extracellular traps formation, and improves the tumor immune microenvironment.